Bosnian studies : perspectives from an emerging field - Karabegović, Dženeta; Karamehić-Oates, Adna (Columbia : University of Missouri Press, 2022)
"The diverse entry points of scholars in their questions and research related to Bosnia and Herzegovina, the war and its aftermath suggest that 'Bosnian Studies' is an emerging field, encompassing the aforementioned approaches to research and study. The ambition of this coedited volume is therefore to not only examine the emergence of 'Bosnian Studies' as a field through the individual chapters of scholars in different disciplines, but also to highlight how diaspora scholars in particular are contributing to the field's dynamism and trends"--
Introduction / Adna Karamehic-Oates -- The Bosnian genocide as the cornerstone for Bosnian studies / Hikmet Karčić and Richard Newell -- Fieldwork in no-man's land? ethical standards and international research in Bosnia and Herzegovina / Mišo Kapetanović -- Neither Bosnian nor American: parents' perceptions of children's adaptation experience in the United States / Ajlina Karamehic-Muratovic, Florian Sichling, Sidreta Zuko, and Evangelia Vamvas -- Beyond borders: heritage practices amongst Sarajevans and Sarajevan diaspora / Asya Hekimoglu -- The role of storytelling in healing, recognition, inclusion and empowerment / Amra Sabic-El-Rayess -- Translocal Bosnian communities and their impact on current emigration trends / Dženeta Karabegović and Amra Mešić -- External voting and homeland politics in Bosnia and Herzegovina: voter suppression through procedural disenfranchisement as background to diaspora mobilization efforts to reverse the political effects of ethnic cleansing / Aida Ibričević and Senada Zatagić -- Writing home: Bosnian writers in diaspora / Hariz Halilovich -- Nowhere in Bosnia: language, time, and memory in the work of Aleksandar Hemon / Emina Melonic -- Who is 'Bosnian Studies' for? alternative futures for diasporic scholarship / Dino Kadich -- Bosnian studies -- where do we go from here? / Dženeta Karabegović
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 21, 2022).
eBooks on EBSCOhost
Keywords: Bosnians -- Foreign countries; Yugoslav War, 1991-1995 -- Bosnia and Herzegovina; Bosnia and Herzegovina -- History -- 1992-; Bosnia and Herzegovina -- Emigration and immigration; Bosnia and Herzegovina -- History -- 1992- -- Study and teaching; Bosniaques -- Pays étrangers.; Guerre dans l'ex-Yougoslavie, 1991-1995 -- Bosnie-Herzégovine.; Education; Emigration and immigration; Bosnia and Herzegovina; Since 1992; History